2021
DOI: 10.3389/frph.2021.661360
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Common Gynecological Conditions in the Middle East: Systematic Review and Meta-Analysis

Abstract: Introduction: High prevalence of gynecological conditions in women of Middle Eastern origin is reported, likely due to regional risk factors and mediators. The objective of this systematic review and meta-analysis is to investigate the prevalence of polycystic ovary syndrome (PCOS), endometriosis, uterine fibroids, and adenomyosis in women of Middle Eastern origin.Methods: MEDLINE, EMBASE, PsycINFO, Global Health, and Google Scholar databases were searched from database inception until 14 February 2021 to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 123 publications
0
8
0
Order By: Relevance
“…Because the current diagnosis of EMS requires surgical visualization and the confirmation of pathological results [3], the measurement of the incidence and prevalence of endometriosis is complicated, and estimates vary widely among different studies. Based on the prevalence of pelvic pain and infertility in the general population, the estimated population prevalence of endometriosis is approximately 10% [4,5] and is higher in symptomatic women [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the current diagnosis of EMS requires surgical visualization and the confirmation of pathological results [3], the measurement of the incidence and prevalence of endometriosis is complicated, and estimates vary widely among different studies. Based on the prevalence of pelvic pain and infertility in the general population, the estimated population prevalence of endometriosis is approximately 10% [4,5] and is higher in symptomatic women [6].…”
Section: Introductionmentioning
confidence: 99%
“…Fig 6. Funnel plot using data from the 16 studies evaluating the association between endometriosis and breast cancer…”
mentioning
confidence: 99%
“…In a systematic review with meta-analysis, the pooled prevalence of endometriosis was estimated to be 12.9% (95% CI: 4.2-25.4) in Middle Eastern women undergoing laparoscopy, for any indication (13). While the findings of this review demonstrated that the region lacks reliable, population-based data on the symptomatology and risk factors of endometriosis, there are inherent difficulties in the universal application of symptom and phenotype-based criteria across different countries and cultures, as demonstrated for polycystic ovary syndrome among Arab women (13)(14)(15)(16)(17). No studies have assessed the diagnostic delay, work productivity or activity impairment among Middle Eastern women with endometriosis.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on gynecological conditions are underrepresented in low- and middle-income Middle Eastern countries affected by war and political instability, such as Iraq, Syria, Libya, Sudan, Lebanon, Yemen, and Palestine, unlike in higher-income countries like the Gulf countries, Turkey, and Egypt, where women have greater access to healthcare and may be more thoroughly screened [ 30 ]. In these conflict-affected areas, young women may suffer from chronic pain and menstrual irregularities, but cultural norms may prevent them from seeking help, prolonging their suffering [ 30 ].…”
Section: Reviewmentioning
confidence: 99%